2022
DOI: 10.3389/fpsyg.2021.794165
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Staff Perspectives on Spiritual Care Competencies in Norway: A Pilot Study

Abstract: Spirituality and spiritual care have long been kept separate from patient care in mental health, primarily because it has been associated with psycho-pathology. Nursing has provided limited spiritual care competency training for staff in mental health due to fears that psychoses may be activated or exacerbated if religion and spirituality are addressed. However, spirituality is broader than simply religion, including more existential issues such as providing non-judgmental presence, attentive listening, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…On the other hand, external factors such as the policy of institutions and provision of educational programs were also found to be essential for enhancing nurses’ spiritual care abilities [ 28 – 31 ]. Nevertheless, given the importance of providing spiritual care for psychiatric patients [ 17 ], it is surprising that the associations of personal and external factors with spiritual care competency of mental health nurses have received little attention in the past [ 32 ]. Another observational study comparing the self-rated competence towards spiritual care between nurses of various subspecialties showed that spiritual nursing care competency and its link to other factors may vary in different health sectors [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, external factors such as the policy of institutions and provision of educational programs were also found to be essential for enhancing nurses’ spiritual care abilities [ 28 – 31 ]. Nevertheless, given the importance of providing spiritual care for psychiatric patients [ 17 ], it is surprising that the associations of personal and external factors with spiritual care competency of mental health nurses have received little attention in the past [ 32 ]. Another observational study comparing the self-rated competence towards spiritual care between nurses of various subspecialties showed that spiritual nursing care competency and its link to other factors may vary in different health sectors [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, despite the findings that personality traits are associated with the provision of spiritual care nursing and patients’ satisfaction [ 34 , 35 ], none of the studies focused on mental health nurses. Overall, there was limited research on factors that may be related to spiritual care competency in mental health nurse [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive (knowledge)-Assessing and planning spiritual care [5,47] Intrapersonal Resources [48] Interpersonal Resources [48] Transpersonal Resources [48] Understanding the concept of spiritual care [5,27,36,47,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Awareness of different approaches to spiritual assessment [21,27,36,47,[50][51][52][53][54][55]59,61,62,[65][66][67][68] Integration of being human into the evolutionary axis of its existence [5,21,46,47,50,53,…”
Section: Data Synthesis and Reportingmentioning
confidence: 99%
“…The use of all the EPICC materials ( www.epicc‐neteork.org ) could improve students' spiritual competencies, enhance individual personal and professional growth in the spiritual domain, and increase the ability to care for patients (Chiang et al, 2020 ; Giske & Cone, 2012 ; McSherry et al, 2020 ; Wu et al, 2016 ). Spiritual care is not only within the domain of nurses and midwives, but it is needed across all of healthcare (Baldacchino, 2015 ; Cone & Giske, 2021a , 2021b ; Dewittea et al, 2021 ; Gordon et al, 2020 ; Holmberg et al, 2021 ; Hvidt et al, 2020 ; Neathery et al, 2020 ; Nolan et al, 2011 ; Patterson et al, 2018 ; Poncin et al, 2019 ) to promote whole person and patient‐centred care.…”
Section: Implications For Education Practice and Researchmentioning
confidence: 99%
“…Results of the parametric statistics testing the reliability and validity of the Tool included extensive discussion of the quantitative data and a brief overview of qualitative findings, all of which are presented in another paper (Giske et al, 2022 ). The Tool was also pilot tested among mental health staff (Cone & Giske, 2021b ). The purpose of this paper was to report on the qualitative findings from students' open comments, since rich data provided an opportunity to explore similarities and differences among the responses from each country where the tool was tested.…”
Section: Introductionmentioning
confidence: 99%